2022
DOI: 10.22146/gamaijb.63788
|View full text |Cite
|
Sign up to set email alerts
|

Defining Event Marketing as Engagement-Driven Marketing Communication

Abstract: Event marketing has been one of the popular corporate marketing strategies for decades. The method is experiential and aims to transform not only attendees' perceptions but also their behavior. Despite this, several events have failed to build loyalty or the purchase intention beyond the entertainment value. In addition, event marketing now focuses on gaining purchase and visit intentions. When a company focuses on engagement, it causes an increased usage desire and longer customer lifetime value. However, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
4
0
1
Order By: Relevance
“…This finding is consistent with other research indicating that both digital green marketing campaigns and tourist pro-environmental behavior have an impact on the intention of tourists to revisit ecodestinations. (Butkouskaya et al, 2021;Foster et al, 2020;Kumar & Sadarangani, 2021; M. T. Lee et al, 2020;Setiawan et al, 2022;Shien et al, 2022;Yu, 2022). H9: Tourist Environmental Belief has a positive effect on Revisit Intention to Eco-Destination mediated by Tourist Pro-Environmental Behavior Table 7 supports hypothesis 9, indicating that tourist environmental belief has a positive effect on revisit intention to an eco-destination, mediated by tourist pro-environmental behavior.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…This finding is consistent with other research indicating that both digital green marketing campaigns and tourist pro-environmental behavior have an impact on the intention of tourists to revisit ecodestinations. (Butkouskaya et al, 2021;Foster et al, 2020;Kumar & Sadarangani, 2021; M. T. Lee et al, 2020;Setiawan et al, 2022;Shien et al, 2022;Yu, 2022). H9: Tourist Environmental Belief has a positive effect on Revisit Intention to Eco-Destination mediated by Tourist Pro-Environmental Behavior Table 7 supports hypothesis 9, indicating that tourist environmental belief has a positive effect on revisit intention to an eco-destination, mediated by tourist pro-environmental behavior.…”
Section: Discussionmentioning
confidence: 69%
“…Hence, the formulation of this hypothesis is as follows: Hypothesis 1: Digital Green Marketing Campaigns have a positive effect on Tourist Proenvironmental Behavior Digital Green Marketing Campaign and Revisit Intention to Eco-Destination Companies commonly utilize marketing communications to shape consumer needs. As part of the company's marketing strategy, event marketing can be used to develop a consumer connection with the product or service brand (Setiawan et al, 2022). In the context of tourism, Ariyeni et al (2020) found that green marketing initiatives can enhance tourists' desire to revisit Pariaman Beach.…”
Section: Wwwieecaorg/journalmentioning
confidence: 99%
See 1 more Smart Citation
“…Kegiatan dasar yang dilakukan untuk menarik minat dan juga memperbaiki kualitas perguruan tinggi di tengah persaingan adalah pemasaran (marketing) (Setiawan et al, 2022;Wichmann et al, 2022). Dalam konsep pemasaran, dikenal suatu marketing mix yang berisi aspek/variabel pemasaran untuk mencapai tingkat penjualan yang ingin dicapai (Thabit & Raewf, 2018;Wichmann et al, 2022).…”
Section: Pendahuluanunclassified
“…There are two forms of language in general, namely spoken language and written language (Albiladi, 2018;Gustiasari, 2018;Ngongo & Ngongo, 2022). Despite the differences in how these two languages are used, both have the same communicational goal: to ensure that the speaker's message is properly and clearly understood by the other person (Kasmahidayat & Marcia, 2018;Setiawan et al, 2022). Communication is considered as a tool utilized by humans to achieve certain goals, such as imparting knowledge, persuading, or acquiring power."…”
Section: Introductionmentioning
confidence: 99%